2023
DOI: 10.3389/fnut.2023.1253255
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis on the literature of monk fruit extract and mogrosides as sweeteners

Andy Wai Kan Yeung

Abstract: The evolution of research literature on monk fruit extract and mogroside as sweeteners has yet to be investigated. No study has evaluated this literature from a bibliometric perspective. This bibliometric study analyzed the relevant research literature indexed in Web of Science, to unveil its growth and the most productive authors, institutions, countries, journals, and journal categories. In addition, this study aimed to identify the recurring themes of the literature. On July 2023, the Web of Science Core Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…These developments will expand the market for S. grosvenorii as a sweetener. Since 2010, there has been a steady increase in the number of publications and citations on S. grosvenorii , particularly focusing on its health effects and biosynthesis of Mogs ( Yeung, 2023 ). However, at present, there is limited clinical trial evidence regarding the pharmacological effects of S. grosvenorii .…”
Section: Discussionmentioning
confidence: 99%
“…These developments will expand the market for S. grosvenorii as a sweetener. Since 2010, there has been a steady increase in the number of publications and citations on S. grosvenorii , particularly focusing on its health effects and biosynthesis of Mogs ( Yeung, 2023 ). However, at present, there is limited clinical trial evidence regarding the pharmacological effects of S. grosvenorii .…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings to stevia extract compositions and their effects on host metabolism, monk fruit extract sweetness is due to possessing the mogroside glycoside of cucurbitane derivatives. Mogroside V is about 250 times sweeter than sucrose and is non-caloric [ 39 ]. Also, the in vitro and in vivo studies have suggested mogrosides possess antioxidant and anti-inflammatory effects, as well as the extracts mogroside V and 11-oxo-mogroside V possessed inhibitory effects on mouse skin carcinogenesis models [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mogroside V is about 250 times sweeter than sucrose and is non-caloric [ 39 ]. Also, the in vitro and in vivo studies have suggested mogrosides possess antioxidant and anti-inflammatory effects, as well as the extracts mogroside V and 11-oxo-mogroside V possessed inhibitory effects on mouse skin carcinogenesis models [ 39 ]. From the triterpenoid glycoside extract from monk fruit, Liu et al [ 40 ] found that mogroside IVe inhibited colorectal cancer HT29 cells and throat cancer Help-2 cell proliferation in a dose-dependent manner in culture and xenografted mice.…”
Section: Discussionmentioning
confidence: 99%